Factors That Influence Ability Cognitive Students in Social Studies Subject - Djeba, Wahyuni; Zeffitni, Zeffitni; Ika Listiqowati (PT. Riset Press International, 2025)
Learning process in progress in a way effective, namely in progress in a way slow, steady, and appropriate with objective education, then quality education can achieved. One of the factor main factors that influence the learning process is student That alone, but can also be caused by other factors such as teachers, environment, facilities and infrastructure, and the learning media used. Formulation problem study How influence use of Sway multimedia learning media towards ability cognitive students in Social Studies at SMP Negeri 14 Palu, how influence motivation to cognitive student in eye Social Studies lessons at SMP Negeri 14 Palu. Research objectives analyze the influence of multimedia learning media- based Sway on cognitive students in Social Studies at SMP Negeri 14 Palu. Research This use quasi- experimental approach which is development from true experiment. Research results So reliability is constancy or stability or consistency a tool or instrument For used in measurement, reliability test data can seen in the reliable test technique used namely Cronbach's Alpha and obtained reliability of 0.751 which includes in category very high reliability. In N of Items alpha there is Results 31. Conclusion of the research In the learning process student trained logical ability to solve problems. In the curriculum independence is also given or entered elements life society, nation and state as well as element religious For to form students with character. Therefore, these are learning media multimedia based sway according implemented at SMP Negeri 14 Palu.